1997
DOI: 10.2105/ajph.87.12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tuberculosis infection among New York State prison employees.

Abstract: OBJECTIVES: This study examined tuberculosis skin test conversions among 24,487 New York State prison employees in 1992. METHODS: Conversions were analyzed by prison and by job category. RESULTS: The conversion rate was 1.9%. Employees in prisons with low and high numbers of prisoner cases had odds ratios for conversion of 1.67 (95% confidence interval [CI] = 1.27, 2.19) and 2.20 (95% CI = 1.69, 2.87), respectively, relative to employees in prisons with no prisoner cases. In prisons with cases, guards and medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 2 publications
1
20
0
7
Order By: Relevance
“…111 who presented IPVD without hepatopulmonary syndrome, IPVD was scored as 1+. (14) In the present study, echocardiographydetermined IPVD score was found to correlate significantly with shunt fraction calculated using either of the two quantitative methods employed (blood gas analysis after pure oxygen breathing and scintigraphy).…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…111 who presented IPVD without hepatopulmonary syndrome, IPVD was scored as 1+. (14) In the present study, echocardiographydetermined IPVD score was found to correlate significantly with shunt fraction calculated using either of the two quantitative methods employed (blood gas analysis after pure oxygen breathing and scintigraphy).…”
Section: Resultssupporting
confidence: 49%
“…This value was defined as proposed in the literature, due to its acceptable sensitivity for the identification of gas exchange abnormalities in such patients. (7,10,14) Patients underwent perfusion scintigraphy with technetium-99m-labeled macroaggregated albumin ( 99m Tc-MAA). The radioactive drug (2-4 mCi) was injected into a peripheral vein, with the patient in the sitting position.…”
Section: Methodsmentioning
confidence: 99%
“…Transmission occurs among prisoners (10)(11)(12)(13) and among professionals working in the prison system. (14) Longer prison stays are significantly associated with an increased risk for latent and active TB. (15,16) A study conducted in prisons in the city of New York showed that one year of incarceration doubled the probability of developing active TB among inmates who were not infected before entering the prison system.…”
Section: Introductionmentioning
confidence: 99%
“…The M. tuberculosis complex is responsible for more disease worldwide than any other bacteria [1,2]. Although the United States is a low prevalence country (reporting 14,511 confirmed cases of tuberculosis in 2004 [3]), tuberculosis is a recognized occupational hazard in health care [4] and correctional facilities [5]. In addition, it is often necessary to differentiate between M. tuberculosis and ubiquitous nontuberculous mycobacterial infection.…”
Section: Introductionmentioning
confidence: 99%